The Legal Disputes of Land Right’s Overlapping Ownership on the Complete Systematic Land Registration Program (PTSL) - Ambarwati, Mega Dewi (Acta Universitatis Danubius. Juridica, 2023)
Objectives This study has objective to analyze the obstacles during the complete systematic land registration program (PTSL) program, that is, the overlapping ownership of land rights, Prior Work The PTSL program provides legal certainty of land ownership for Indonesian society. As written in the 1945 Constitution of the Republic of Indonesia, Article 33, Paragraph (3) mandates land use for people's prosperity, Approach The methodology used is a descriptive analysis by explaining the data in the field, Results The results show that a double certificate (overlapping ownership) was found after the PTSL program. Therefore, it is recommended that the Land Office should be more thorough and accurate for land measurement and mapping, Implications Land history is essential to ensure legal certainty regarding land ownership. This cannot be ignored because many land disputes have occurred because of overlapping cases, Value The PTSL program can be used to determine land certification impediments due to overlapping ownership. Thus, people will know the latest status of their land.